PURCHASING DECISION ON B2B BUSINESS MODEL PT P - Syuhada, Muhammad Khalief; Alldila Nadhira Ayu Setyaning (Publikasi Inspirasi Indonesia, 2025)
This study aims to identify and analyze the factors influencing purchasing decisions in the B2B (Business to Business) business model at PT P, particularly in the oil, gas, and petrochemical sectors. Through a five-month internship program, the author was directly involved in marketing activities and client relationship management. The research methods employed include in-depth interviews with relevant informants and field observations. The findings indicate that several key factors affect purchasing decisions, including the identification and approach to potential clients, the influence of price and product quality, as well as the company's capabilities. The study also highlights the importance of lead time management, technical evaluation of offers, and product guarantees as competitive advantages for PT P. These findings are expected to provide insights for the company in formulating more effective marketing strategies to win project tenders in the B2B market.